2013
DOI: 10.1111/acel.12103
|View full text |Cite
|
Sign up to set email alerts
|

Life-long caloric restriction reduces oxidative stress and preserves nitric oxide bioavailability and function in arteries of old mice

Abstract: Aging impairs arterial function through oxidative stress and diminished nitric oxide (NO) bioavailability. Life-long caloric restriction (CR) reduces oxidative stress, but its impact on arterial aging is incompletely understood. We tested the hypothesis that life-long CR attenuates key features of arterial aging. Blood pressure, pulse wave velocity (PWV) (arterial stiffness), carotid artery wall thickness and endothelium-dependent dilation (EDD) (endothelial function) were assessed in young (Y: 5–7 mo), old ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
187
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 153 publications
(202 citation statements)
references
References 67 publications
14
187
0
1
Order By: Relevance
“…2A), indicating excessive superoxide‐mediated endothelial dysfunction with aging. To further assess the influence of aging and NMN treatment on oxidative stress in arteries, aortas were used because of the greater amount of tissue provided for biochemical assay, as described previously (Sindler et al ., 2011; Donato et al ., 2013; LaRocca et al ., 2013; Gano et al ., 2014). Consistent with the results of the pharmacological‐function experiments with TEMPOL, compared with young mice, aortas from old animals exhibited increased superoxide production, directly assessed by electron paramagnetic resonance (EPR) spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A), indicating excessive superoxide‐mediated endothelial dysfunction with aging. To further assess the influence of aging and NMN treatment on oxidative stress in arteries, aortas were used because of the greater amount of tissue provided for biochemical assay, as described previously (Sindler et al ., 2011; Donato et al ., 2013; LaRocca et al ., 2013; Gano et al ., 2014). Consistent with the results of the pharmacological‐function experiments with TEMPOL, compared with young mice, aortas from old animals exhibited increased superoxide production, directly assessed by electron paramagnetic resonance (EPR) spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that arterial SIRT1 activity is reduced with aging and contributes to the age‐related impairment in endothelial function (Donato et al ., 2011; Gano et al ., 2014). We and others also have shown that lifelong CR prevents (Csiszar et al ., 2009; Donato et al ., 2013) and short‐term CR reverses (Rippe et al ., 2010) the age‐associated decline in endothelial function and that these effects are associated with enhanced arterial SIRT1 activity. Consistent with these observations, we recently found that 4 weeks of treatment with the SIRT1 activator SRT1720 restores endothelial function (i.e., EDD) in old mice (Gano et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations